Developing a Comprehensive Financial Inclusion Index - Miruna M. VASILCA; Ioana M. MINDRICAN; Elena F. MATEI (Communications of International Proceedings, 2021)
As defined in this paper, financial inclusion is the ease of access to, usage of and the availability of financial products and services by all individuals of the economy. Since the financial inclusion topic is gaining popularity, the literature on financial inclusion has offered ample evidence of the benefits of an inclusive financial system. Nevertheless, the literature lacks a comprehensive method for measuring the extent of financial inclusion across economies. This paper aims to fill this gap and, as a result, makes an innovative contribution to the literature. Following a multidimensional methodology, this study presents an index of financial inclusion (IdFI) that was used to compare levels of financial inclusion across heterogeneous economies such as EU ones’ at a particular point in time (2017). In the group of 28 countries, Luxembourg leads with the highest value of IdFI followed by the United Kingdom, Spain, France, Italy, Austria and Germany (Appendix). Only these seven countries belong to the high IdFI group with IdFI values of 0.6 or more. Another 15 countries: Belgium, Denmark, Ireland, Portugal, Slovenia, Croatia, Sweden, Netherlands, Malta, Estonia, Finland, Poland, Latvia, Slovak Republic and Cyprus form the group of medium IdFI countries with IdFI values between 0.4 and 0.6. All other countries have low IdFI values, lying between 0.07 and 0.38.
Keywords: Financial inclusion; financial system; banking; financial products; financial services; banking